2003
DOI: 10.1007/s00280-003-0642-8
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of capecitabine (Xeloda) in Japanese and Caucasian patients with breast cancer

Abstract: No clinically relevant differences in the pharmacokinetics of capecitabine and its key metabolites 5'-DFUR, 5'-DFCR, and 5-FU were found between Japanese and Caucasian patients. Plasma concentrations of FBAL were higher in Caucasian than in Japanese patients but this difference is not clinically relevant as FBAL has no antiproliferative activity and systemic exposure to FBAL does not correlate with the tolerability of capecitabine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
32
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 28 publications
7
32
0
2
Order By: Relevance
“…Following doses of 1250 to 1255 mg/m 2 , the mean area under the curve of 5Ј-DFCR ranged from 6.51 to 14.1 mg/h/l with a coefficient of variation up to 77% (Reigner et al, 2003). According to our data, 5Ј-DFCR is equally well formed by CES1A1 and CES2.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Following doses of 1250 to 1255 mg/m 2 , the mean area under the curve of 5Ј-DFCR ranged from 6.51 to 14.1 mg/h/l with a coefficient of variation up to 77% (Reigner et al, 2003). According to our data, 5Ј-DFCR is equally well formed by CES1A1 and CES2.…”
Section: Discussionsupporting
confidence: 51%
“…This three-step targeted prodrug approach was developed to increase the bioavailability of 5-fluorouracil by reducing the catabolism of 5-fluorouracil in the liver by dihydropyrimidine dehydrogenases and targeting 5-fluorouracil formation to the tumor. Pharmacokinetic analyses indicate high interpatient variability in the exposure to capecitabine and its metabolites in plasma (Reigner et al, 2003).…”
mentioning
confidence: 99%
“…Considering the fact that, capecitabine exhibits linear increases in C max and AUC 0-¥ when dosage increases, 4 it is possible to normalize the previously reported pharmacokinetic data to a dose of 1500 mg. Therefore, it can be concluded that the pharmacokinetic parameters obtained in this study were similar to the published pharmacokinetic studies 26,28 and it seems that there are no racial differences in capecitabine pharmacokinetics.…”
Section: Application Of the Methodssupporting
confidence: 72%
“…13 There is no evidence of drug accumulation across a range of doses, and pharmacokinetics were found to be similar between Caucasian and Japanese patient populations. 14,15 The half-life of capecitabine is between 0.49 and 0.89 hours, while the half-life of the metabolite (5-FU) extends from 0.67 to 1.15 hours. 13,14,16 Of additional interest, capecitabine is supposed to be dosed within 30 minutes of food.…”
Section: Mode Of Action and Pharmacokineticsmentioning
confidence: 99%